Existence, Uniqueness and Stability Results for Nonlinear Neutral Fractional Volterra-Fredholm Integro-Differential Equations - Hamoud, Ahmed A.; Sharif, Abdulrahman A. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we established some new results concerning the existence and uniqueness of the solutions of nonlinear Volterra-Fredholm integro-differential equations of Caputo fractional order. These new results are obtained by using the Leray-Schauder nonlinear alternative, Krasnoselskii’s and Banach fixed point theorems. In addition, we investigate generalized Ulam stability for this fractional system.